2021
DOI: 10.1186/s12954-021-00573-6
|View full text |Cite
|
Sign up to set email alerts
|

Harm reduction must be recognised an essential public health intervention during crises

Abstract: The COVID-19 had a substantial impact on the provision of harm reduction services for people who use drugs globally. These front-line public health interventions serve a population that due to stigma, discrimination and criminalisation, faces barriers to accessing health and social services and are particularly vulnerable to public health crises. Despite this, the pandemic has seen many harm reduction services close, reduce operations or have their funding reduced. Simultaneously, around the world, harm reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…These constraints, paired with an increased need to provide flexible syringe distribution in light of COVID-19 social distancing restrictions, left several programs unable to offer program participants the volume of syringes needed to avoid syringe reuse. This example and other data from this study highlight how COVID-19 has reinforced the pathways between structural-level stigma (e.g., policies that limit syringe distribution flexibility) and individual-level harms for PWUD ( Collins et al, 2022 ; Wilkinson et al, 2020 ; Broz et al, 2021 ; Csak et al, 2021 ).…”
Section: Discussionsupporting
confidence: 51%
“…These constraints, paired with an increased need to provide flexible syringe distribution in light of COVID-19 social distancing restrictions, left several programs unable to offer program participants the volume of syringes needed to avoid syringe reuse. This example and other data from this study highlight how COVID-19 has reinforced the pathways between structural-level stigma (e.g., policies that limit syringe distribution flexibility) and individual-level harms for PWUD ( Collins et al, 2022 ; Wilkinson et al, 2020 ; Broz et al, 2021 ; Csak et al, 2021 ).…”
Section: Discussionsupporting
confidence: 51%
“…Indeed, a previous study suggested that multi services are more e cient than single services to help PWUD [30]. Finally, as with most HR services, mail-based HR structures may be threatened by the risk of funding limitations [31].…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 Public Health Agency of Catalonia, Epidemiological Surveillance Service, Barcelona, Spain. 2 Public Health Agency of Catalonia -Programme On Addictions, HIV, STI and Viral Hepatitis, Barcelona, Spain.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Harm reduction services for PUD are a front-line public health interventions. They serve a population that due to stigma, discrimination and criminalisation, face barriers to accessing health and social services and are particularity vulnerable in public health crises [ 2 ]. The lockdown measures limited access to substances and also access to resources, including HR services [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%